To simplify the expression 1/2 (x + 4) + 1/4(4x - 2), we need to distribute the coefficients.
1/2 (x + 4) = 1/2 * x + 1/2 * 4 = 1/2x + 2
1/4(4x - 2) = 1/4 * 4x + 1/4 * (-2) = x - 1/2
Now we can combine the like terms:
1/2x + 2 + x - 1/2
Combining like terms means adding or subtracting the coefficients of the same variables.
So, 1/2x + x = (1/2 + 2/2)x = 3/2x
And 2 - 1/2 = 4/2 - 1/2 = 3/2
Therefore, the simplified expression is 3/2x + 3/2 or in standard form, (3/2)x + 3/2.
1/2 (x + 4) + 1/4(4x - 2)
1 answer